Psychological Consequences of Chronic Hepatitis C: Comparison of Using and Not Using Interferon Injections - Malik, Subha; Arshad, Hana (Annals of King Edward Medical University, 2018)
Background: The number of Chronic Hepatitis C (CHC) patients is increasing in Pakistan. The treatment of the disease has further psychological consequences which contribute to poor health of such patients. This paper explores the perceptions of CHC patients on their disease. Objectives: To investigate the psychological consequences of using Interferon injections and not using them in CHC patients. Methods: Through purposive sampling, six case studies (3 males and 3 females) were conducted with CHC patients. The study was completed in the month of February, 2017 in the outpatient department of Liver in a leading Government Hospital of Lahore. The diagnosed CHC patients were interviewed after taking written consent. Semi-structured interview schedule was prepared beforehand by reviewing past literature. Thematic Analysis combining inductive and deductive approaches were used. Results: The themes depicting depression and anxiety were found in CHC patients using interferon injections whereas stress was found in CHC patients not using these injections. The common major themes were personality traits, quality of life and coping strategies in both CHC patients. However, the sub-themes were found to be different in both CHC patients. Conclusion: CHC patients having interferon injections were suffering from more adverse psychological consequences than CHC patients not taking interferon injections.